Analysis of the tourism attractiveness of a itera reservoir, South Lampung - Nindita Murti; Ria Ripardi (International Journal of Applied Sciences in Tourism and Events, 2025)
Unplanned tourist spaces often emerge from everyday community use rather than formal planning. This study examines the spatial transformation and tourism attractiveness of Embung A ITERA, a campus water reservoir that has organically developed into a local recreational destination. Using a descriptive qualitative approach, data were collected through six days of field observation, interviews with 15 informants, and documentation, and analyzed using the 4A framework (Attraction, Accessibility, Amenities, Ancillary Services). Quantitative observations show high average daily visitation (≈185 visitors/day), with the highest peak in the afternoon (111 visitors/hour), indicating strong community reliance on the site for exercise and leisure. The findings address research gaps regarding (1) unplanned tourism emerging from routine spatial practices, (2) the transformation of conservation infrastructure into recreational destinations, and (3) the limited integration of spatial–ecological–social perspectives in campus tourism studies. This study introduces Organic Campus Tourism, highlighting how eco-infrastructure within academic environments can evolve into multifunctional tourism spaces through community participation and spatial adaptation. The research contributes by expanding the 4A framework into eco-infrastructure contexts and offering practical guidance for managing multifunctional campus open spaces through inclusive design and sustainable visitor management.